The analysis of monetary framework of inflation targeting, exchange rate regime switching and volatility in selected sub-Saharan African countries - Umar, Mohammed (2016)
Exchange rate volatility has affected not only sub-Saharan African economies but the volume of international transactions in general. It directly affects the nations’ profitability of tradable commodities, balance of payment, terms of trade and investment decisions. Despite the measures taken by the monetary authorities to ensure macroeconomic stability, exchange rate remains volatile. This study, therefore pursues the following objectives. First, it investigates the effectiveness of the inflation targeting framework (ITF) as a hedging strategy for exchange rate volatility. Second, examines whether the monetary policy of ITF has performed the role of the nominal anchor in the economies. Third, examines the influence of exchange rate regime switching on exchange rate volatility and finally, determines causality among the variables of the monetary theory of exchange rate determination. In achieving the results of the objectives, the study employed a battery of econometric procedures namely, threshold generalised autoregressive conditional heteroscedasticity (TGARCH) model, generalised method of moments (GMM) estimators, time-varying Markov-switching transition probability ARCH model and asymmetric/Toda-Yamamoto dynamic causality with leverage bootstrapping. The results of the first objective indicate that the menace of exchange rate volatility reduces when the IT policy was adopted in Ghana and South Africa. However, the ITF policy transition increases the volatility of exchange rate. Secondly, the findings on the baseline and augmented Taylor rule models reveal that ITF become a nominal anchor in the economies immediately after the adoption of the policy, although the hypothetical response of interest rate to inflation deviation and output gap is greater in South Africa compared to Ghana. Thirdly, the results of the time-varying Markov-switching models indicate that the exchange rates of the countries are characterised by decline in the downward regime except for Nigeria which shows high decline in the upward regime. Finally, the estimates of the asymmetric/Toda-Yamamoto causality reveal the existence of size distortion when the asymptotic Granger causality is used. The main policy implication of the findings is that monetary authorities can ensure exchange rate stability through accountability and transparency in contractionary or expansionary policies in aggregate demand using monetary policy instrument.